The Pharmacist’s Role in the Management of Postpartum Depression: An Integrative Approach (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Postpartum depression (PPD) is a significant public health issue affecting 10-20% of women after childbirth. This review explores the pivotal role of pharmacists in managing PPD, emphasizing their involvement in medication management, patient education, and interprofessional collaboration. By integrating pharmacists into the multidisciplinary care team, there is potential to enhance patient outcomes, adherence to treatment, and overall quality of life for new mothers.